The Influence of Accountability, Transparency, Responsiveness, and Reliability on the Integrity of Madrasah Principals - Arizal, Jepri; Rafida, Tien; Fadhli, Muhammad (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to analyze the effects of accountability, transparency, responsiveness, and reliability on the integrity of madrasah principals in Binjai City, both partially and simultaneously, from the perspective of Islamic Education Management. This study employed a quantitative approach with an explanatory research design. The population consisted of 127 madrasah principals at the RA, MI, MTs, and MA levels under the auspices of the Ministry of Religious Affairs of Binjai City. A total of 96 respondents were selected using proportionate stratified random sampling and the Slovin formula with a 5% margin of error. Primary data were obtained through a Likert-scale questionnaire distributed to madrasah principals, while secondary data were derived from madrasah institutional documents under the Ministry of Religious Affairs of Binjai City and relevant scholarly literature on leadership integrity, educational governance, and Islamic Education Management. The data were analyzed using descriptive-inferential statistics and multiple regression analysis. The findings indicate that accountability is the strongest predictor of madrasah principals’ integrity. Transparency and responsiveness also have positive and significant effects, whereas reliability does not have a significant partial effect. Simultaneously, accountability, transparency, responsiveness, and reliability have a significant effect on the integrity of madrasah principals, with the model explaining 58.4% of the variance. This study concludes that the integrity of madrasah principals is more strongly shaped by accountable, transparent, and responsive governance practices than by personal reliability alone. Therefore, strengthening the integrity of madrasah principals should be directed toward improving responsibility, information openness, responsiveness to stakeholders’ needs, and leadership consistency based on the Islamic value of amanah.